Flow Cytometric Analysis of the Oxidative Status in Human Peripheral Blood Mononuclear Cells of Workers Exposed to Welding Fumes - du Plessis, Lissinda; Laubscher, Petrus; Jooste, Jacques; du Plessis, Johan; Franken, Anja; van Aarde, Nico; Eloff, Fritz (Journal of occupational and environmental hygiene, 2010)
Flow cytometry is a simple analytical technique that identifies, counts, and characterizes cells. The oxidative status of cells is influenced by many exogenous sources, such as occupational exposure to welding fumes. This study evaluated flow cytometry as a method to determine the oxidative status of male welders (n = 15) occupationally exposed to welding fumes. Flow cytometric analysis of reactive oxygen species (ROS) was carried out in peripheral blood mononuclear cells (PBMC) by using the probe 2, 7-dichlorodihydrofluorescein diacetate (DCFH-DA). Lipid peroxidation was measured by the decrease of fluor-DHPE fluorescence and intracellular glutathione (GSH) levels by using mercury orange. All of the parameters were also observed under a confocal microscope. The oxidative stress ratio was calculated from the oxidative damage and the antioxidant capacity to give an accurate account of the cellular oxidative status. ROS and lipid peroxidation levels were elevated by ∼ 87% and ∼ 96%, respectively, and GSH levels lowered ∼ 96% in PBMC of workers exposed to welding fumes compared with non-exposed controls. The oxidative stress ratio was significantly higher (p < 0.001) in the exposed group. Flow cytometry can be useful for the measurement of cellular oxidative stress in somatic cells of workers exposed to welding fumes and other occupational settings. Calculating an oxidative stress index may be useful in predicting disease outcomes and whether preventative control measures are efficient.